THE EFFECT OF ALKALIS ON THE SILICA CONTENT OF MANTLE-DERIVED MELTS - NMR, RAMAN, AND INFRARED SPECTROSCOPY - Hirschmann M.M.; Baker M.B.; Stolper E.M. (My University, 1998)
A large body of experimental evidence shows that at low and moderate pressure (<1.5 GPa), alkali-rich silicate liquids coexisting with Mg-rich olivine and orthopyroxene are richer in silica than typical basalts. This phenomenon is caused by the tendency of alkali ions to reduce the number of Si-O-Si linkages in the melt, which translates to negative deviations from ideality for mixing between alkalis and silica and which requires increases in alkalis to be accompanied by increases in silica for liquids in equilibrium with mantle peridotite. P2O5 and TiO2 have an effect opposite to alkalis, and when these elements are also enriched in the liquid, the high silica contents caused by alkali-enrichment may be reduced or eliminated. The effect of alkalis on the silica content of melts equilibrated with magnesian olivine and orthopyroxene is reduced at higher pressure, such that silica enrichments in alkali-rich melts will be small if the equilibration pressure is greater than ~1.5 GPa. This pressure effect is largely the result of decreases with pressure in the extent of polymerization for all olivine + orthopyroxene-saturated liquids. As pressure increases and liquids in equilibrium with olivine and orthopyroxene become less polymerized, proportionally fewer alkalis break up highly polymerized (Q4) silica tetrahedra, and, therefore, alkalis have less effect on the activity coefficient of silica. Secondarily, the observed changes with pressure may also be related to changes in the energetics of alkali-silica interactions.Because equilibration of alkali-rich melts with mantle peridotite only produces high silica at low and moderate pressures, small degree partial melts of anhydrous peridotite formed during adiabatic upwelling will not typically be silica-rich. However, if liquids rich in alkalis, perhaps formed by selective leaching of Na2O and K2O from peridotite during upward percolation, equilibrate with the mantle at depths <1.5 GPa, they will become silica-rich. Such silica-rich liquids, now preserved as glass inclusions in spinel peridotite xenoliths, are probably restricted to the shallowest part of the mantle (<45 km).